Does a monster eat my hair? : a picture book on leukemia - Brunner, Grit 2002-; Flickinger, Joachim (Freiburg Karger, 2022)
Mia has been tired for days. One evening after her bath she notices little red dots all over her body. The next morning Mia's mom takes her to the doctor. He examines Mia and sends her straight to the hospital. The doctor there finds out that she is suffering from leukemia. Mia senses that her parents are worried and that her brother Nick is afraid that it's his fault that Mia is ill. At the hospital Mia learns a lot about her illness, the treatment and how she is going to recover. She meets other children and makes new friends. When Mia is well again, her parents and her brother Nick pick her up at the hospital. At home a surprise is waiting for her.
Título original: Frisst ein Krebs die Haare auf?
Keywords: LEUCEMIA EN NIÑOS -- LITERATURA JUVENIL; LEUCEMIA EN NIÑOS -- DIAGNÓSTICO -- LITERATURA JUVENIL; LEUCEMIA EN NIÑOS -- TRATAMIENTO -- LITERATURA JUVENIL